KUALITAS PELAYANAN PUBLIC SAFETY CENTER PADA PUSAT PELAYANAN KESELAMATAN TERPADU DINAS KESEHATAN PROVINSI SULAWESI TENGAH - Damaris Damaris; Abdul Rivai; Muh Nawawi (CV. ALIM'SPUBLISHING, 2024)
This research purpose is to analyze the “ Serving Quality of public Safety Center At Integrated Healthy Service, Healthy Dines Central Sulawesi Province. The writer use the service quality theory which stated by Zeithaml-Paraurman-Berry (1990).He stated that there are five (5) dimension to measure the service quality,they are tangables, reliability,responsiveness,assurance and empathy. The quality research in its method which brought out a descriptive data through an interview to a respondent. The research located in UPT. Of Public Safety Center At Integrated Healthy Service, Healthy Dines Central Sulawesi Province and also at user of PSC 119 house. There are 4 informants who gives the service and 3 informants who has its service, so there are 7 people totally. Interview,observation and documentation are used for its data collection. Then, The results of the research show that the quality of Public Safety Center services at the Integrated Safety Service Center of the Central Sulawesi Provincial Health Service from the tangible dimension is not good where the facilities and infrastructure supporting PSC 119 in providing services are not adequate, the responsiveness dimension is also not good where there are still service users who say that the officers slow in responding to service users, while the dimensions of Reliability, Assurance and Empathy are good